Polyacrylamide gel electrophoresis of visna virus polypeptides isolated by agarose gel chromatography. - Lin, F H (J Virol, 1978)
The proteins of visna are separated into nine major peaks by agarose gel chromatography in 6 M guanidine hydrochloride (GuHCl). The polypeptides in eack peak were isolated by acid precipitation and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The patterns of SDS-PAGE show that the excluded material from the GuHCl column contains an aggregate of 10 non-glycosylated polypeptides. It is shown that this aggregate represents virus substructures that are not completely solubilized by GuHCl. Two glycoproteins, gp175 and gp115, were isolated from the column eluate. The major glycoprotein gp115 was coeluted with P90, P68, and P61 in GuHCl 4. Each of the four major peaks (GuHCl 5 to 8) contains more than one nonglycosylated polypeptide. However, a small polypeptide, P12, can be isolated in a homogeneous form in the last peak, GuHCl 9. Analysis of the virus proteins (100 microgram) by SDS-PAGE shows that 20 radioactive bands can be recognized. During fractionation of the protein on agarose gel columns followed by analysis with SDS-PAGE, a number of minor polypeptides that were not detected before became clearly recognizable. Thus, the combined use of column chromatography and SDS-PAGE shows that visna virus is composed of 25 proteins. IMAGES: